Do food security indicators vary between male and female-headed households? Evidence from legume farmers in Western Kenya - Susan Atieno Oburu; David Jakinda Otieno; Evans Chimoita; John Ojiem (Frontiers in Sustainable Food Systems, 2024)
IntroductionFood security is an important aspect of sustainable development at global, national and local levels. However, differences in resource endowments and control thereof, may privilege some households and regions than others. As a result, households’ diets may be varied leading to differences in food security status. Various initiatives that seek to diversify diets through legume integration on farms have been promoted in developing countries; but, their effects on household food security remains undocumented. In order to address the above knowledge gap, this study compares the food security indicators of male and female-headed households that integrate legumes in their farms in Nandi County, Kenya.MethodsUsing cross-sectional data from 374 respondents, various food security scores were computed. Subsequently, the ordinary least squares regression model was applied to determine factors that influence the food security scores.Results and discussionThe results revealed that the food security scores were in the normal range; acceptable food consumption score of 62.20 and medium household dietary diversity score of 5.24. In both the male- and female-headed households; land size, access to credit and distance to nearest open-air market from the household significantly affected food security scores positively, while number of meals per day had significant negative effect. Further, in the male-headed households, the food security score was positively affected by household size and years of farming experience, while the household head’s age negatively affected the food security score. These findings provide useful insights on the need to target specific interventions that support the attainment of desired levels of food security in male- and female-headed households based on their distinct levels of resource endowments and control.